Cell-Membrane-Coated Metal-Organic Framework Nanocarrier Combining Chemodynamic Therapy for the Inhibition of Hepatocellular Carcinoma Proliferation - Huaying Xie; Xuhua Xiao; Xiaoyuan Yi; Kunzhao Huang; Liyan Wang (MDPI AG, 2024)
Chemodynamic therapy (CDT) employs hydrogen peroxide (H2O2) within the tumor microenvironment (TME) to initiate the Fenton reaction and catalyze the generation of hydroxyl radicals (·OH) for targeted therapy. Metal ion-based nanomaterials have garnered significant attention as catalysts due to their potent anti-tumor effects. Hypoxia in the TME is often associated with cancer cell development and metastasis, with HIF-1α being a pivotal factor in hypoxia adaptation. In this study, an organic framework called MIL-101 (Fe) was designed and synthesized to facilitate H2O2-induced ·OH production while also serving as a carrier for the HIF-1α inhibitor Acriflavine (ACF). A biomimetic nanomedical drug delivery system named MIL-101/ACF@CCM was constructed by encapsulating liver cancer cell membranes onto the framework. This delivery system utilized the homologous targeting of tumor cell membranes to transport ACF, inhibiting HIF-1α expression, alleviating tumor hypoxia, and catalyzing ·OH production for effective tumor eradication. Both in vivo and in vitro experiments confirmed that combining ACF with chemotherapy achieved remarkable tumor inhibition by enhancing ROS production and suppressing HIF-1α expression.